Vocal Polyps: Clinical, Morphological, and Immunohistochemical Aspects - Garcia Martins, Regina Helena [UNESP]; Faveri, Julio de [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; de Albuquerque e Silva, Rafael (Mosby-elsevier, 2011)
Objectives. To study the clinical, morphological, and immunohistochemical characteristics of vocal polyps.Study Design. Prospective and retrospective.Methods. Clinical study: 76 medical charts from patients with polyps were reviewed. Histology study: in 42 slides from surgical specimens, the following were analyzed: epithelium, basal membrane, and lamina propria. In the transmission and scanning electron microscopy (TEM and SEM) studies, eight new cases of polyps were included. An immunohistochemical study was carried out in the 42 specimens, using antibody antifibronectin, antilaminin, and anticollagen IV.Results. Genders-43% males and 57% females; age range between 21 and 40 years (36.85%); and between 41 and 60 years of age (51.31%); smoking and drinking reported by 39 and 15 patients, respectively; associated symptoms-vocal abuse (61%), gastroesophageal (47%), and nasosinusal symptoms (32%); occupation teachers (24.0%) and maids (18.0%). Histology epithelial hyperplasia (31.71%), hyperkeratosis, (14.28%), edema (100%), vessel proliferation (92.86%), and congestion (83.33%). SEM reduction in mucous lacing and increase in desquamating cells. TEM hyperplastic epithelium, enlargement of the intercellular junctions, dense subepithelial network of collagen and basal membrane with adhesion loss. Immunohistochemistry greater immunoexpression of fibronectin, laminin, and collagen IV around the vessels.Conclusions. In vocal polyps, the morphological analyses show lamina propria with edema, vessel proliferation and inflammation, basement membrane with adhesion loss in some areas and dense network of subepithelial collagen. Immunohistochemistry techniques identify pigmentation of the antibodies anti-fibronectin, anti-laminin, and anticollagen IV in the endothelium of blood vessels.
Keywords: Larynx; Polyps; Morphology; Scanning; electron microscopy; Immunohistochemical